FROM LOVE TO LABOR: NEGOTIATING PAID CARE WORK WITHIN SRI LANKA'S CULTURAL CONTEXT - Wijerathna, H. M. S. C.; Wanniarachchi, W. S. A. (The Library, University of Kelaniya, Sri Lanka., 2025)
Care work, encompassing child-rearing, eldercare, and domestic labour remains systematically undervalued and feminized across societies, yet its cultural and economic marginalization takes on distinct dimensions in Sri Lanka. This study explores the barriers to recognizing and remunerating care work as formal labour in Sri Lanka, where religious ethics frame caregiving as a moral duty and merit-making rather than an economic activity. Drawing on feminist economic theory, particularly Nancy Folbre's "love's labor" and Arlie Hochschild's "emotional surplus value", the paper highlights that care work is rendered invisible through the interplay of religious ideology, neoliberal policy paradigms, and gendered norms. Through qualitative content analysis of scholarly texts, policy documents, and feminist critiques, the research reveals how Sri Lankan women disproportionately bear unpaid care burdens, a disparity exacerbated during the COVID-19 pandemic. Despite care work's foundational role in sustaining society, efforts to integrate it into labor protections or social security systems face resistance, often dismissed as culturally incompatible or economically unfeasible. The study identifies an epistemological failure in dominant economic frameworks that treat care as a private responsibility rather than a public good. It critiques neoliberal development models for prioritizing market productivity while relying on unpaid care labor to subsidize gaps in public services. The findings underscore the need for discursive shifts, advocating for policy interventions that engage religious leaders, feminist economists, and caregivers in redefining care as collective infrastructure. Recommendations include public awareness campaigns and inclusive policy design that challenges the moralization of women's self-sacrifice. By situating Sri Lanka's care economy within global feminist debates, this research contributes a culturally specific lens to broader struggles for recognizing care work as essential labour, asserting that its equitable compensation is both a feminist imperative and a prerequisite for socioeconomic justice.
Keywords: care work; feminist economics; unpaid labour; Sri Lanka; gender justice